Edukasi dan Pendampingan Literasi Keuangan dan Digital pada Mantan Pekerja Migran Indonesia - Riani, Lilia Pasca; Mustofa, Mustofa; Supriyanto, Supriyanto; Fikri, Aula Ahmad Hafid Saiful; Sholeh, Maimun (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Indonesian Migrant Workers (PMI) are one of the nation's heroes because they are recognized as a source of foreign exchange for the Indonesian nation. The problems faced are getting caught in debt/online loans, fraud under the guise of investment, and consumerist lifestyles. Looking at the explanation of the problems above, the problem solving solution provided in this Community Service activity is to provide education and assistance regarding financial literacy, ethics, psychology and digital literacy. Activities are carried out in the form of workshops and mentoring for 6 months. The results achieved were the implementation of a workshop with a comprehensive evaluation covering aspects of material, resource persons and facilities where the majority of participants responded very well and were willing to take part in further mentoring activities. From the results of the evaluation of the activity, it can be concluded that this activity is very much needed by participants from PMI because, so they get direct benefits and are more able to control themselves to manage finances including being able to apply digital ethics and refrain from doing negative things in the digital world.